2019
DOI: 10.1101/728857
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A cross-species neural integration of gravity for motor optimisation

Abstract: 15Recent kinematic results, combined with model simulations, have provided support for the 16 hypothesis that the human brain uses an internal model of gravity to shape motor patterns that 17 minimise muscle effort. Because many different muscular activation patterns can give rise to 18 the same trajectory, here we analyse muscular activation patterns during single-degree-of-19 freedom arm movements in various directions, which allow to specifically investigating 20 gravity-related movement properties. Using a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 105 publications
1
8
0
Order By: Relevance
“…In young adults, several studies have shown that singledegree-of-freedom arm movements exhibit directional asymmetries in the vertical plane. These asymmetries: (i) were consistently reported as a more abrupt acceleration phase for upward than for downward movements; (ii) do not exist in the horizontal plane (Gentili et al, 2007;Le Seac'h and McIntyre, 2007); (iii) progressively disappear in the vertical plane when participants are exposed to microgravity (Papaxanthis et al, 2005;Gaveau et al, 2016); (iv) were observed very early in the movements [before 70 ms after movement start Gaveau et al, 2014)]; and (v) were explained by optimal control model simulations and EMG analyses as a motor strategy that minimizes muscle effort (Berret et al, 2008;Crevecoeur et al, 2009;Gaveau et al, 2014Gaveau et al, , 2016Gaveau et al, , 2019. Altogether, in young adults, previous results strongly suggest that direction-dependent kinematics represent the signature of a motor planning strategy that optimally integrates gravity torque to save muscle effort.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In young adults, several studies have shown that singledegree-of-freedom arm movements exhibit directional asymmetries in the vertical plane. These asymmetries: (i) were consistently reported as a more abrupt acceleration phase for upward than for downward movements; (ii) do not exist in the horizontal plane (Gentili et al, 2007;Le Seac'h and McIntyre, 2007); (iii) progressively disappear in the vertical plane when participants are exposed to microgravity (Papaxanthis et al, 2005;Gaveau et al, 2016); (iv) were observed very early in the movements [before 70 ms after movement start Gaveau et al, 2014)]; and (v) were explained by optimal control model simulations and EMG analyses as a motor strategy that minimizes muscle effort (Berret et al, 2008;Crevecoeur et al, 2009;Gaveau et al, 2014Gaveau et al, , 2016Gaveau et al, , 2019. Altogether, in young adults, previous results strongly suggest that direction-dependent kinematics represent the signature of a motor planning strategy that optimally integrates gravity torque to save muscle effort.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, directiondependent kinematics has been proposed to represent the signature of a motor planning strategy that optimally integrates gravity torque to save muscle effort. Recent electromyographic (EMG) analyses further support this concept (Gaveau et al, 2019).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Young adults are known to use an optimal strategy that minimizes muscle effort. Directional asymmetries can quantify this strategy, i.e., differences between upward and downward movements [ 60 , 61 , 62 , 63 ]. Poirier et al (2020) observed that young and older participants exhibited qualitatively similar directional asymmetries, thereby indicating that older adults can unfold the same effort-related optimization strategy as young adults.…”
Section: Mechanistic Studies Of Motor Function In Healthy Agingmentioning
confidence: 99%
“…McIntyre 2007); iii) progressively disappear in the vertical plane when participants are exposed to microgravity (Papaxanthis et al 2005;Gaveau et al 2016); iv) were observed very early in the movements (before 70ms after movement start (Gaveau and Papaxanthis 2011;Gaveau et al 2014); v) were explained by optimal control model simulations and EMG analyses as a motor strategy that minimizes muscle effort (Berret et al 2008;Crevecoeur et al 2009;Gaveau et al 2014Gaveau et al , 2016Gaveau et al , 2019. Altogether, in young adults, previous results strongly suggest that direction-dependent kinematics represent the signature of a motor planning strategy that optimally integrates gravity torque to save muscle effort.…”
Section: Discussionmentioning
confidence: 99%